A Critical Discourse Analysis of Incitement in English News Reports - Al-Shammary, Zahraa Ali; Al-Aadili, Nesaem Mehdi (Indian Journal of Information Sources and Services, 2025)
The current study aims to investigate incitement found in English news reports (particularly, the direct quotations in the body/lead development of these reports) from a critical discourse analysis perspective. Incitement, which is the form of communication that is viewed as an expression of hatred and as a way to stir up feelings and persuade the hearer to commit a criminal action, has not been studied from a critical discourse analysis view as far as the researcher knows. Consequently, the current study is an attempt to fill this gap by answering the following questions: (1) What is the most dominant general type of incitement utilized in English news reports? (2) Which sub-type of incitement is most frequently employed in English news reports? (3) What are the discursive strategies that are exploited to show incitement in English news reports? (4) What are the frequencies of occurrence of the discursive strategies employed to realize incitement in English news reports? To answer the questions of the study, an eclectic model is utilized to analyze six inciting texts that were originally published on YouTube channels. Hence, Lasswell's Model of Communication and Van Dijk`s discursive strategies are activated to accomplish this aim. These strategies illustrate how different ideologies are created across a range of discourses and show how ideologies such as hatred and prejudice motivate incitement in English news reports. Likewise, two methods are employed to analyze the data; namely, the qualitative and the quantitative. The current study comes up with some conclusions, the most important of which are that explicit incitement is the most dominant general type of incitement in English news reports. Incitement is also realized via various discursive strategies including syntactic, semantic, pragmatic and rhetorical strategies.